Formulation of ethical integrated marketing communication strategy to boost member acquisition for PT HM Sampoerna Tbk.’s smoke-free products - Ferick Omar Chehab (Privietlab, 2026)
This study investigates the persistently low acquisition of members for PT HM Sampoerna Tbk’s smoke-free products in Indonesia and formulates an ethical, regulation-compliant integrated marketing communication (IMC) strategy to strengthen member growth among adult smokers. Employing a descriptive exploratory design, the research combined a 5 Whys root-cause diagnosis with a cross-sectional online survey of adult smokers and smoke-free product users (N=202). Data were analyzed using descriptive statistics and a Weighted Score Model to prioritize ethical principles, communication design elements, and channel choices. The results show that ethics is treated as a non-negotiable baseline, with near-equal weights for honesty, fairness, and social responsibility. In communication design, message source credibility ranks highest, narrowly ahead of creative execution, whereas message strategy ranks third. Channel priorities favor interaction-rich, adult-only touchpoints: personal selling and permission-based direct marketing outperform digital marketing, with advertising and public relations being the least preferred under regulatory constraints. Therefore, digital channels are positioned mainly for gated educational content, appointment setting, and retention-oriented CRM rather than as primary conversion engines. This study proposes an IMC roadmap that reallocates efforts toward below-the-line activations, trained product specialists, and structured follow-ups, supported by early ethical screening and continuous compliance monitoring. The findings offer actionable guidance for managers designing harm-reduction communications in tightly regulated contexts and provide a basis for future longitudinal assessments of behavioral change and member lifetime value impacts.